Ambulance dispatch of older patients following primary and secondary telephone triage in metropolitan Melbourne, Australia: a retrospective cohort study - Peter Cameron; Kathryn Eastwood; Dhanya Nambiar; Rosamond Dwyer; Judy A Lowthian (BMJ Open)
Background Most calls to ambulance result in emergency ambulance dispatch (direct dispatch) following primary telephone triage. Ambulance Victoria uses clinician-led secondary telephone triage for patients identified as low-acuity during primary triage to refer them to alternative care pathways; however, some are returned for ambulance dispatch (secondary dispatch). Older adult patients are frequent users of ambulance services; however, little is known about the appropriateness of subsequent secondary dispatches.Objectives To examine the appropriateness of secondary dispatch through a comparison of the characteristics and ambulance outcomes of older patients dispatched an emergency ambulance via direct or secondary dispatch.Design A retrospective cohort study of ambulance patient data between September 2009 and June 2012 was conducted.Setting The secondary telephone triage service operated in metropolitan Melbourne, Victoria, Australia during the study period.Participants There were 90 086 patients included aged 65 years and over who had an emergency ambulance dispatch via direct or secondary dispatch with one of the five most common secondary dispatch paramedic diagnoses.Main outcome measures Descriptive analyses compared characteristics, treatment and transportation rates between direct and secondary dispatch patients.Results The dispatch groups were similar in demographics, vital signs and hospital transportation rates. However, secondary dispatch patients were half as likely to be treated by paramedics (OR 0.51; CI 0.48 to 0.55; p<0.001). Increasing age was associated with decreasing treatment (p<0.005) and increasing transportation rates (p<0.005).Conclusion Secondary triage could identify patients who would ultimately be transported to an emergency department. However, the lower paramedic treatment rates suggest many secondary dispatch patients may have been suitable for referral to alternative low-acuity transport or referral options.